Proyek Sistem Informasi Pemesanan Seragam Dinas Perkantoran Pada Cv. Rahayu Berkah Mandiri Berbasis Web - Ahmad Safi'i; Irfan Effendi; Muhammad Hadiansyah Arrasyid; Indah Purnamasari (KALBISCIENTIA Jurnal Sains dan Teknologi, 2023)
The process of ordering office uniforms on CV. Rahayu Berkah Mandiri uses conventional methods, namely coming directly the location, contacting by telephone or Whatsapp. Customers have difficulty finding information on the availability of goods. This study aims to build a system that provides uniform information with description of its quality. System development carried out using the Unified Modeling Language can certainly be solution. The results of this study are in the form website that is used to make the process of ordering office uniforms. This website can be an alternative for customers in placing orders so that customers do not need to come to the company or contact the company and the owner can also process a more structured order process. Based on the results of research testing and evaluation, the system built can help customers to order goods and be received by the owner quickly.